A two-stage traveling-wave thermoacoustic electric generator with loudspeakers as alternators. (1st January 2015) - Kang, Huifang; Cheng, Peng; Yu, Zhibin; Zheng, Hongfei
Highlights: A two-stage traveling wave thermoacoustic generator is introduced. Two audio loudspeakers have been used as linear alternators. A high electric power output of 204 W has been achieved. A thermal-to-electric efficiency of 3.43% has been achieved. Abstract: This paper presents the design, construction and tests of a traveling-wave thermoacoustic electric generator. A two-stage traveling-wave thermoacoustic engine converts thermal energy to acoustic power. Two low-impedance linear alternators (i.e., audio loudspeakers) were installed to extract and convert the engine's acoustic power to electricity. The coupling mechanism between the thermoacoustic engine and alternators has been systematically studied numerically and experimentally, hence the optimal locations for installing the linear alternators were identified to maximize the electric power output and/or the thermal-to-electric conversion efficiency. A ball valve was used in the loop to partly correct the acoustic field that was altered by manufacturing errors. A prototype was built based on this new concept, which used pressurized helium at 1.8 MPa as the working gas and operated at a frequency of about 171 Hz. In the experiment, a maximum electric power of 204 W when the hot end temperature of the two regenerators reaches 512 °C and 452 °C, respectively. A maximum thermal-to-electric efficiency of 3.43% was achieved when the hot end temperature of the two regenerators reaches 597 °C and 511 °C, respectively. The research results presented in this paper demonstrate that multi-stage traveling-wave thermoacoustic electricity generator has a great potential for developing inexpensive electric generators.